The impact of entrepreneurial characteristics and competencies on business performance in the creative industry in Indonesia - Ayumi Fitriani Gunawan (Asia Pacific Journal of Innovation and Entrepreneurship)
Purpose – The purpose of this study is to examine the impact of the characteristics and competencies of entrepreneurs on business performance within the creative industry in Indonesia. By creative industry, is refer to market-oriented enterprises that use creativity and intellectual capital to create, produce, distribute and disseminate creative goods and services through media channels. Design/methodology/approach – This study measured six entrepreneurial characteristics: creative and innovative, risk-taking, need for achievement, leadership, autonomy and proactiveness. In addition, it measured five entrepreneurial competencies: opportunity, strategy, relationship, organization and learning. Data collection was conducted using a questionnaire administered to 294 entrepreneurs operating businesses within the creative industry in Java, Sumatra and Kalimantan, Indonesia. Findings – The findings of this study demonstrated that entrepreneurial characteristics and competencies had a significantly positive effect on business performance. Creativity and innovation emerged as the most influential characteristics, whereas strategy stood out as the most influential competency. Originality/value – This study aimed to examine whether the personal qualities of entrepreneurs as identified within conventional industries − specifically their entrepreneurial characteristics and competencies − had an impact on business performance in the creative industry in Indonesia. Conventional industries, unlike creative industries, are characterized by the production and distribution of physical goods or basic services, with less emphasis on creative innovation as the core driver.